Common Employment Policies of the EU – Challenges and Opportunities for Hungary - Fóti, KLÁRÁ (Papeles del Este, 2006)
Numerous objectives, targets and measures are envisaged in the National Action Plan for Employment in order to address the low employment level, which is considered as one of the biggest problems of the labour market in Hungary. It remains to be seen, however, how effective these measures will be especially in the short run because many of the factors underlying this problem require long term solution. For example, employability of the unskilled people cannot be improved overnight, and the same is true for large regional disparities. It will take a long time to overcome regional labour market diversification, and this would obviously require an efficient use of the EU-funds, which is far beyond the scope of the employment policy, and would need close coordination with other economic and social policy measures.